Penggunaan Permainan Tradisional Moneka untuk Meningkatkan Hasil Belajar Matematika Siswa Sekolah Dasar - Rahmat Abdul (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2020)
This Classroom Action Research (CAR) aims to: 1) introduce the game Moneka to elementary students; 2) describe the steps of the Moneka traditional game for learning Mathematics, 3) measure the improvement of students' Mathematics learning outcomes through the traditional Moneka game with Mathematics learning. This work uses a classroom action research design (PTK) with research subjects for third grade students at SDN No. 32 Kota Selatan totaling 24 students. Researchers as a key instrument in this case as a giver of action or a model teacher who is assisted by two observers. Data collection instruments include observation sheets of teacher and student activities, test questions, and documentation. Data analysis uses qualitative analysis with the steps of: data reduction, data presentation, and drawing conclusions. The results of this study indicate that: 1) the use of traditional Moneka games in class III SDN No. 32 Kota Selatan, very well implemented, 2) The Implementation of Moneka Traditional Games in Mathematics Learning can improve student mathematics learning outcomes, this is evidenced by an increase in the value of learning outcomes from cycle I and cycle II. In the first cycle reached 73% and silkus II reached 81%.